2000
DOI: 10.1002/(sici)1097-0029(20000301)48:5<282::aid-jemt5>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies on the translocation of tubulovesicular system toward the intracellular canaliculus during stimulation of the gastric parietal cell

Abstract: The gastric parietal has two characteristic membrane systems. One is the intracellular canaliculus, which is specialized networks of enfolded luminal membrane channels lined with numerous microvilli. The other structures common to all parietal cells are the tubulovesicles or the tubulovesicular membranes, a system of tubules and vesicles. The tubulovesicular compartment is drastically depleted during maximal gastric acid secretion and this is coincident with an increase in the canalicular cell surface membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Studies on rat, rabbit, and human parietal cells have demonstrated that histamine induces (1) redistribution of the proton pump H + /K + -ATPase from cytoplasmic localizations to the canalicular membrane, (2) association of F-actin to the canalicular membrane, (3) stimulation-associated colocalization of ezrin and F-actin, and (4) immense expansion or swelling of the canalicular lumen [6,10,11]. Inhibition of gastric acid secretion is often associated with alterations in one or more of these processes [6].…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Studies on rat, rabbit, and human parietal cells have demonstrated that histamine induces (1) redistribution of the proton pump H + /K + -ATPase from cytoplasmic localizations to the canalicular membrane, (2) association of F-actin to the canalicular membrane, (3) stimulation-associated colocalization of ezrin and F-actin, and (4) immense expansion or swelling of the canalicular lumen [6,10,11]. Inhibition of gastric acid secretion is often associated with alterations in one or more of these processes [6].…”
Section: Introductionsupporting
confidence: 90%
“…Furthermore, the number of tubulovesicles was reduced and an elongation of the microvilli at the surface of the canalicular membrane was observed, which tends to indicate that the surface of the canalicular membrane was increased and that a fusion between tubulovesicles and the apical membrane had occurred [10].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The other is the tubulovesicular system composed of tubules and vesicles formed by smooth endoplasmic reticulum and a cystic‐like membrane structure, mostly seen in the resting stage. Ogata and Yamasaki investigated the plasma membrane system of rat parietal cells in the resting stage and that stimulated by tetragastrin under electron microscopy and proved the connection between these two plasma membrane systems. The process of acid secretion was powered by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Dilatation of intracellular canaliculi of parietal cell might be due to the stimulation of the cell by histamine leading to re-arrangement of cytoskeleton and recruitment of (H + /K + -ATPase) rich tubulo-vesicles to the apical membrane expanding the intracellular canaliculi with loss of luminal microvilli (Ogata & Yamasaki, 2000). This dilatation occurs in the active phase of secretion.…”
Section: Discussionmentioning
confidence: 99%